Interactive football-training based on rebounders with hit position sensing and audio-visual feedback - Jensen, M. M.; Grønbæk, K.; Thomassen, N.; Andersen, J.; Nielsen, J. (International Journal of Computer Science in Sport, 2014)
The last decade`s advancements in computer technology have facilitated a growing interest in the development of interactive sports-training equipment. This development has provided athletes and coaches with measurement and training tools, with performance analysis or skill improvement as purpose. However, most of these tools are created with a single goal, either to measure or train, and are often used and tested in very controlled settings. In this paper, we present an interactive football-training platform, called Football Lab, featuring ensormounted rebounders as well as audio-visual feedback. Football Lab enables the creation of novel training games, which aim to improve players` technical skills, and simultaneously function as a tool for measuring player performance and development over time. A logging of the Football Lab was conducted through 92 weeks, where the platform was available for the general public, analysis of a subset of the 20.000 games played in the period are discussed. Moreover, the paper contains a discussion covering challenges in data collection, transferability issues for interactive training equipment, as well as examples of experiments conducted with the platform. Finally, directions for future research within the area of interactive training equipment are proposed.